2015
DOI: 10.1242/dev.126342
|View full text |Cite
|
Sign up to set email alerts
|

Mcidas and GemC1/Lynkeas are key regulators for the generation of multiciliated ependymal cells in the adult neurogenic niche

Abstract: Multiciliated cells are abundant in the epithelial surface of different tissues, including cells lining the walls of the lateral ventricles in the brain and the airway epithelium. Their main role is to control fluid flow and defects in their differentiation are implicated in many human disorders, such as hydrocephalus, accompanied by defects in adult neurogenesis and mucociliary disorder in the airway system. Here we show that Mcidas, which is mutated in human mucociliary clearance disorder, and GemC1 (Gmnc or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
149
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(163 citation statements)
references
References 47 publications
10
149
2
2
Order By: Relevance
“…The same dynamics exists between MCCs and transporting cells in the zebrafish pronephros (Liu et al 2007). Notch inhibition also drives MCC specification in mouse oviducts and brain ventricles (Kessler et al 2015;Kyrousi et al 2015). Recently, bone morphogenetic protein (BMP) signaling has been shown to interact with the Notch pathway to control mucociliary differentiation of vertebrate epithelia (Cibois et al 2015).…”
Section: Multiciliated Epithelia Across Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…The same dynamics exists between MCCs and transporting cells in the zebrafish pronephros (Liu et al 2007). Notch inhibition also drives MCC specification in mouse oviducts and brain ventricles (Kessler et al 2015;Kyrousi et al 2015). Recently, bone morphogenetic protein (BMP) signaling has been shown to interact with the Notch pathway to control mucociliary differentiation of vertebrate epithelia (Cibois et al 2015).…”
Section: Multiciliated Epithelia Across Animalsmentioning
confidence: 99%
“…As their name suggests, both have coiled-coil domains related to geminin, a protein involved in cell-cycle progression and in the balance between proliferation and differentiation (Kroll 2007). GEMC1 was primarily found to promote initiation of DNA replication in vertebrate cells (Balestrini et al 2010) and was recently found to be necessary for MCC postmitotic commitment in zebrafish pronephros, Xenopus skin, and mouse brain MCCs (Kyrousi et al 2015;Zhou et al 2015). IDAS was first found to bind to geminin and to regulate its function in DNA replication licensing in S phase (Pefani et al 2011).…”
Section: Multiciliated Cells In Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two related coiled-coil proteins, Multicilin and Gemc1, are both necessary and sufficient to initiate MCC differentiation, acting as co-regulators in a transcriptional complex with a subset of the E2F proteins (Arbi et al, 2016;Kyrousi et al, 2015;Ma et al, 2014;Stubbs et al, 2012;Terre et al, 2016;Zhou et al, 2015). The complex between Multicilin, E2f4 and DP1 (EDM) in particular appears to directly activate gene expression required for centriolar biogenesis (Ma et al, 2014), thus driving a novel form of organelle assembly that enables MCCs to form the hundreds of basal bodies required for multiple ciliation.…”
Section: Introductionmentioning
confidence: 99%